Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Interlaboratory comparison of centrifugal ultrafiltration with ICP-MS detection in a first-step towards methods to screen for nanomaterial release during certification of drinking water contact materials - Austin H. Henke; Kenneth Flores; Aaron J. Goodman; Kelly Magurany; Kerri LeVanseler; James Ranville; Jorge L. Gardea-Torresdey; Paul K. Westerhoff (Science of The Total Environment, 2024)

Detection of the clinically persistent, pathogenic yeast spp. Candida auris from hospital and municipal wastewater in Miami-Dade County, Florida - Kristina Babler; Mark Sharkey; Sebastian Arenas; Ayaaz Amirali; Cynthia Beaver; Samuel Comerford; Kenneth Goodman; George Grills; Michelle Holung; Erin Kobetz; Jennifer Laine; Walter Lamar; et al. (Science of The Total Environment, 2023)

Spatial covariance of herbivorous and predatory guilds of forest canopy arthropods along a latitudinal gradient - Ondrej Mottl; Pavel Fibich; Petr Klimes; Martin Volf; Robert Tropek; Kristina Anderson‐Teixeira; John Auga; Thomas Blair; Phil Butterill; Grace Carscallen; Erika Gonzalez‐Akre; Aaron Goodman; et al. (Ecology Letters, 2020)
In arthropod community ecology, species richness studies tend to be prioritised over those investigating patterns of abundance. Consequently, the biotic and abiotic drivers of arboreal arthropod abundance are still relatively poorly known. In this cross‐continental study, we employ a theoretical framework in order to examine patterns of covariance among herbivorous and predatory arthropod guilds. Leaf‐chewing and leaf‐mining herbivores, and predatory ants and spiders, were censused on > 1000 trees in nine 0.1 ha forest plots. After controlling for tree size and season, we found no negative pairwise correlations between guild abundances per plot, suggestive of weak signals of both inter‐guild competition and top‐down regulation of herbivores by predators. Inter‐guild interaction strengths did not vary with mean annual temperature, thus opposing the hypothesis that biotic interactions intensify towards the equator. We find evidence for the bottom‐up limitation of arthropod abundances via resources and abiotic factors, rather than for competition and predation.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

The Effect of Forest Type on Benthic Macroinvertebrate Structure and Ecological Function in a Pine Plantation in the North Carolina Piedmont - Keli J. Goodman; Anne E. Hershey; Kenneth Fortino (Hydrobiologia, 2006)

Computational Model of Device-Induced Thrombosis and Thromboembolism - Paul D. Goodman; Evan T. Barlow; Peter M. Crapo; S. Fazal Mohammad; Kenneth A. Solen (Annals of Biomedical Engineering, 2005)